Food insecurity and mental health among migrants and refugees in high-income countries: Systematic review and meta-analyses - Resom Berhe; Amit Arora; Kanchana Ekanayake; Kingsley E. Agho (PLoS ONE, 2026)
Background Food insecurity (FI) is a recognised determinant of mental health, yet its specific impact on depression, anxiety, and stress among migrants and refugees in high-income countries (HICs) remains underexplored. This systematic review and meta-analyses examine the association between FI and mental health outcomes in these vulnerable populations. Method A systematic search of five databases (Medline, Scopus, Web of Science, PsycINFO, and Embase) was conducted for observational studies published between January 1, 2008, and December 16, 2025. Inclusion required studies to report on food insecurity and mental health using standard, validated measures. Three independent reviewers screened the studies, extracted the data, and assessed the methodological quality using the Joanna Briggs Institute checklist. Most included studies were cross-sectional. The association between food insecurity and mental health outcomes (depression, anxiety, and stress) was estimated using random-effects models due to substantial heterogeneity (I² > 50%). Funnel plots and Begg’s test were employed to assess potential publication bias. Result We identified 17 eligible studies, totalling more than 4.3 million participants. Overall, FI was significantly associated with higher odds of depression (aOR = 1.44; 95% CI: 1.32–1.57), anxiety (aOR = 2.43; 95% CI: 1.82–3.23), and stress (aOR = 5.9; 95% CI: 2.95–11.94) among migrants and refugees in HICs. Other significant factors were women (aOR = 1.44; 95% CI: 1.32–1.57), Unmarried individuals (aOR = 1.7; 95% CI: 1.49–1.83), and those with poor self-rated health (aOR = 3.6; 95% CI: 2.97–4.36). Moreover, higher household income was significantly associated with lower odds of depression compared to their counterparts (aOR = 0.90; 95% CI: 0.84–0.98; P = 0.007). Conclusion Food insecurity was consistently associated with higher odds of depression, anxiety, and stress among migrants and refugees in high-income countries. These findings support the implementation of enhanced screening and integrated social and mental health responses that address food access and psychological well-being. Trial registration PROSPERO CRD42024525690